Implementation of finite element method for solid mechanics problems in Julia programming language - Antoshkin, A D; Cherednichenko, A V; Savelyeva, I Yu (Journal of physics. Conference series, 2021)
The paper proposes finite element method algorithm implemented in Julia programming language. The main features of Julia programming language are described. The results of Kirsch problem solution are presented. Comparing obtained results with appropriate calculations with open-source finite element software Code Aster are also presented.